EVALUATION OF ANTIOXIDANT AND ANTI-CHOLESTEROL ACTIVITY OF ETHANOLIC LEAF EXTRACT OF GYMNEMA SYLVESTRE – AN IN VITRO STUDY - Princeton, Bianca; R, Gayathri .; Priya, V.Vishnu (International Journal of Psychosocial Rehabilitation, 2020)
Gymnema sylvestre, which is extensively used for serving as traditional remedy for various ailments like diabetes and malaria, belongs to the family Asclepiadaceae and genus gymnema. Recent research has proved that Gymnema can be used as a supplement in the treatment of both type 1 and type 2 diabetes mellitus. Since the herb has potential anti diabetic property research can be done to evaluate its anti-cholesterol and antioxidant potential.Antioxidant and anticholesterol potential of ethanolic leaf extract of the Gymnema sylvestre plant was investigated.The Gymnema sylvestre leaf extract showed a good free radical scavenging activity. The antioxidant potential is comparable to that of VIT C. High cholesterol levels in blood is one of the causes of deadly cardiovascular disease. The result exhibited is the significant anti-cholesterol property of plant extract.From this study, it can be concluded that the Gymnema sylvestre leaf extract possess antioxidant and anti-cholesterol activity. Further in vivo studies can be done so that the extract can be made into a drug.